Overcoming Disinformation and Hoaxes in Political Communication: Promoting Media and Fact Literacy - Dewi, Ni Putu Sinta; Elfiandri, Elfiandri (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2024)
The digital era has accelerated the spread of information, including disinformation and hoaxes, which often appear in the context of political communication. This phenomenon threatens the integrity of the democratic process and the quality of information received by the public. Therefore, the importance of media literacy and fact verification has become increasingly urgent to ensure that citizens can make decisions based on accurate and reliable information. This research aims to evaluate the effectiveness of various media and factual literacy initiatives in reducing the influence of disinformation and hoaxes among voters. The primary focus is identifying the most effective strategies to promote a critical understanding of media content and the ability to verify facts independently. The methods used were field experiments and surveys conducted in several regions with significant variations in media literacy levels. Respondents were selected through stratified random sampling techniques and divided into a control group and an intervention group that received intensive training on media literacy. The results showed that participants who took media and factual literacy training showed significant improvements in identifying and rejecting misinformation. This group is also more critical of information sources and cross-checks facts more often before sharing content. The research conclusion states that media literacy interventions can significantly reduce the influence of disinformation and hoaxes in political communication. In-depth and continuous education is needed to strengthen citizens' abilities to face information challenges in the digital era. Furthermore, collaboration between sectors, including government, educational institutions, and the media, is important to increase awareness and media literacy skills among the wider community.